2023
DOI: 10.1021/acsami.3c01421
|View full text |Cite
|
Sign up to set email alerts
|

Quaternized Chitosan Derivatives as Viable Antiviral Agents: Structure–Activity Correlations and Mechanisms of Action

Abstract: Cationic polysaccharides have demonstrated significant antimicrobial properties and have great potential in medical applications, where the antiviral activity is of great interest. As of today, alcohols and oxidizing agents are commonly used as antiviral disinfectants. However, these compounds are not environmentally safe, have short activity periods, and may cause health issues. Therefore, this study aimed to develop metal-free and environmentally friendly quaternary chitosans (QCs) with excellent long-lastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…S2, ESI †). 16,23 The calculated average DDA of chitosan was E74.3%, which is in close agreement with the manufacturer's reported value of Z75%.…”
Section: Characterizationsupporting
confidence: 89%
See 3 more Smart Citations
“…S2, ESI †). 16,23 The calculated average DDA of chitosan was E74.3%, which is in close agreement with the manufacturer's reported value of Z75%.…”
Section: Characterizationsupporting
confidence: 89%
“…This was consistent with previous determinations. 16,26 Additionally, the change in the downfield shift of the C-6 position from d E 58 ppm in chitosan to d E 62 ppm in QC confirms quaternization.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The conventional method of making water-soluble, antimicrobial chitosan derivatives involves the introduction of permanent positive charges on the polymer backbone using any of the three reactive centers (the two OH groups and the NH 2 group). ,, The HTCC is one of the most often preferred quaternary chitosan derivatives because of its ease of synthesis, permanent cationic charge, and enhanced microbicidal properties. , It is used in various applications like the medical, paper-making, food, and textile industries as a potent antimicrobial inclusion . We have also previously reported the synthesis, characterization, and antibacterial evaluation of fluorinated HTCC derivatives, which were shown to be effective against various clinically isolated bacterial strains. , Recently, using in vitro and ex vivo models of human airway epithelia, Milewska et al (2021) reported that HTCC has antiviral activity against both MERS-CoV and SARS-CoV-2 infections . Recently, the synthesis, characterization, and antiviral activity of quaternized chitosan derivatives were reported by Teotia et al They concluded that the inhibition of specific interactions between viral-host surface proteins and the destabilization of viral surface proteins, by interactions between viral capsid/envelope and the functional quaternary chitosan, is responsible for the overall activity.…”
Section: Introductionmentioning
confidence: 99%